2018
DOI: 10.3389/fpls.2018.00595
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Aberrant Programmed Cell Death Are Associated With Pollen Abortion in Isonuclear Alloplasmic Male-Sterile Wheat

Abstract: Cytoplasmic male sterility is crucial for the utilization of hybrid heterosis and it possibly occurs in parallel with tapetal programmed cell death (PCD) and oxidative metabolism responses. However, little is known about the mechanisms that underlie pollen abortion in wheat. Therefore, we obtained two isonuclear alloplasmic male sterile lines (IAMSLs) with Aegilops kotschyi and Ae. juvenalis cytoplasm. Compared with the maintainer line, cytochemical analyses of the anthers demonstrated that the IAMSLs exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…Similarly, chemical‐induced reduction of ROS accumulation in tobacco ( Nicotiana tabacum ) and tomato ( Solanum lycopersicum ) anthers resulted in delayed tapetum degradation and pollen abortion (Yu, Feng, et al, ). In contrast, when ROS accumulation is increased in anthers such as in the isonuclear alloplasmic male sterile wheat ( Triticum aestivum ) that harbours Aegilops kotschyi cytoplasm, tapetum degradation was observed at the tetrad stage and was followed by pollen abortion (Liu, Shi, Li, Zhang, & Song, ). Increased anther accumulation of ROS was also recently seen in cytoplasmic male sterile Brassica napus along with deficiency in antioxidant enzyme system (Du et al, ).…”
Section: Effects Of Heat Stress On Male Reproductive Developmentmentioning
confidence: 99%
“…Similarly, chemical‐induced reduction of ROS accumulation in tobacco ( Nicotiana tabacum ) and tomato ( Solanum lycopersicum ) anthers resulted in delayed tapetum degradation and pollen abortion (Yu, Feng, et al, ). In contrast, when ROS accumulation is increased in anthers such as in the isonuclear alloplasmic male sterile wheat ( Triticum aestivum ) that harbours Aegilops kotschyi cytoplasm, tapetum degradation was observed at the tetrad stage and was followed by pollen abortion (Liu, Shi, Li, Zhang, & Song, ). Increased anther accumulation of ROS was also recently seen in cytoplasmic male sterile Brassica napus along with deficiency in antioxidant enzyme system (Du et al, ).…”
Section: Effects Of Heat Stress On Male Reproductive Developmentmentioning
confidence: 99%
“…Compared with fertile wheat, physiological studies have shown that sterile wheat accumulates more H 2 O 2 and malondialdehyde (MDA), and the O 2− generation rate is higher [16,17]. Thus, we determined the O 2− generation rate as well as the H 2 O 2 and MDA contents during all of the anther developmental stages (Fig.…”
Section: Ros Assay and Activities Of Antioxidant Enzymesmentioning
confidence: 99%
“…Compared with the physiological research of fertile wheat, the previous research results showed that sterile wheat higher accumulation of H 2 O 2 and MDA and had a higher O 2− generation rate [16,17].…”
Section: Ros Assay and Activities Of Antioxidant Enzymesmentioning
confidence: 99%
“…The input data of gene differential expression was read count data obtained in gene expression level analysis. First, the read count data was standardized by TMM (trimmed mean of M values) [16]. Then these genes were used for the different analysis.…”
Section: Screening and Analysis Of Differential Gene Expressionmentioning
confidence: 99%